Efficacy and safety of glycopyrrolate/eFlow® CS (nebulized glycopyrrolate) in moderate-to-very-severe COPD: Results from the glycopyrrolate for obstructive lung disease via electronic nebulizer (GOLDEN) 3 and 4 randomized controlled trials. (November 2017) - Kerwin, Edward; Donohue, James F.; Goodin, Thomas; Tosiello, Robert; Wheeler, Alistair; Ferguson, Gary T.
Abstract: Background: SUN-101 is a combination of glycopyrrolate delivered through an innovative, electronic nebulizer, intended for the treatment of patients with COPD. The objective of this study was to assess the efficacy and safety of this new drug device combination. Methods: Replicate Phase III randomized, double-blind, placebo-controlled studies were conducted to evaluate the efficacy and safety of glycopyrrolate solution administered by an investigational eFlow ® Closed System (eFlow ® CS) nebulizer in subjects with moderate-to-very-severe COPD, including those with continued background use of a long-acting beta2 -agonist ± inhaled corticosteroid and/or history of cardiovascular (CV) disease. Subjects were randomized in a 1:1:1 ratio to receive placebo or glycopyrrolate (25 μg or 50 μg twice daily [BID]) for 12 weeks. The primary efficacy endpoint was the change from baseline in trough forced expiratory volume in 1 s (FEV1 ) at Week 12 compared with placebo. Secondary endpoints included change from baseline in forced vital capacity (FVC) after 12 weeks, change from baseline in health status measured by St George's Respiratory Questionnaire (SGRQ) at 12 weeks/end of study (EOS), and change in rescue medication use, as well as change from baseline in FEV1 area under the curve from 0 to 12 h after 12 weeks in the GOLDEN 3 sub-study. Daytime and night-time symptoms were recorded using an electronic diary. Safety was monitored throughout the study, including major adverse cardiovascular events. Results: A total of 653 subjects were randomized in GOLDEN 3 and 641 in GOLDEN 4. Treatment with glycopyrrolate 25 μg BID and 50 μg BID resulted in statistically significant and clinically important changes from baseline in trough FEV1 compared with placebo at Week 12 (GOLDEN 3: 0.105 L and 0.126 L; p ≤ 0.0001; GOLDEN 4: 0.084 L and 0.082 L; p ≤ 0.0001). Nebulized glycopyrrolate 25 μg BID and 50 μg BID also resulted in improvements in FVC change from baseline versus placebo at Week 12 (GOLDEN 3: 0.149 L and 0.167 L, p < 0.001; GOLDEN 4: 0.130 L and 0.113 L, p < 0.01), and in SGRQ change from baseline score versus placebo at Week 12/EOS (GOLDEN 3: −3.072 [ p < 0.05] and −1.848; GOLDEN 4: −3.585 and −3.557, p < 0.01). LS mean change from baseline in EXACT-respiratory symptoms total score at Week 12 for placebo and nebulized glycopyrrolate 25 and 50 μg BID were −0.936, −1.903 and −1.502 for GOLDEN 3 and −0.376, −1.647 and −1.532 for GOLDEN 4. Rescue medication use was unchanged. Nebulized glycopyrrolate was well tolerated at both doses based on the incidence of adverse events and CV events. Conclusions: The results of these studies demonstrated statistically significant and clinically important improvements in pulmonary function and patient-reported health outcomes, with an acceptable safety profile, support the use of glycopyrrolate/eFlow ® CS as a potential maintenance treatment for moderate-to-very-severe COPD. Highlights: Two double-blind, Phase III, 12-week studies evaluated the efficacy and safety of nebulized glycopyrrolate (eFlow ® CS). Subjects with moderate-to-very-severe COPD were randomized to placebo or glycopyrrolate (25 μg BD or 50 μg BD). There were statistically significant and clinical improvements in pulmonary function (trough FEV1 ) at Week 12 vs placebo. Significant improvements were also observed in lung function and patient-reported outcome secondary endpoints. Nebulized glycopyrrolate was well-tolerated with an acceptable safety profile.